Salt-Inducible Kinase 2: An Oncogenic Signal Transmitter and Potential Target for Cancer Therapy - Chen, Fangyu; Chen, Liuwei; Qin, Qin; Sun, Xinchen (Frontiers in Oncology, 2019)
The salt-inducible kinase (SIK), which belongs to the sucrose non-fermenting 1 and AMP-activated protein kinase (SNF1/AMPK), is first discovered in the adrenal cortex of a rat on a high-salt diet. As an isoform of the SIK family, SIK2 modulates various biological functions and acts as signal transmitters in different pathways. Compared with adjacent normal tissues, the expression of SIK2 is significantly higher in multiple types of tumor, indicating its pivotal effect in oncogenesis. Recently, a series of studies about SIK2 have emerged to underline its role in several signaling pathways, including PI3K-Akt-mTOR pathway, Hippo-YAP pathway, LKB1-HDAC axis and cAMP-PKA axis. Moreover, a few small-molecule SIK2 inhibitors are found to be able to rescue the oncogenicity of SIK2 during tumor development and reverse its abnormal activation of downstream pathways. However, SIK2 inhibitors may have potential pro-tumor side effect. In this mini-review, we will discuss the results of in vivo and in vitro studies regarding SIK2 mechanism in different signaling pathways, and particularly their regulation in cancer cells. This may provide new ideas for targeting SIK2 as a new therapeutic strategy in tumor therapy.